The Impact of Research-Based Projects (RBP) in Plant Physiology Course on Undergraduate Student Meta-skills - Yennita, Yennita; Astriawati, Fitri; Jumiarni, Dewi; Irawati, Sri (Bioedusiana: Jurnal Pendidikan Biologi, 2025)
Mastery of meta-skills is essential for undergraduate students to prepare themselves for the rapidly changing world driven by advancements in science and technology. Therefore, this study aims to investigate the impact of implementing the research-based project (RBP) model in a plant physiology course on undergraduate students' meta-skills. This study employed a quasi-experimental design with a non-equivalent pre-test and post-test control group design. The research sample consisted of biology education students at the University of Bengkulu selected through purposive sampling. Data were collected using a questionnaire consisting of 79 items, and the research data were analyzed using a One-Way ANCOVA test. The results showed a significant difference in meta-skills between the control and experimental groups, controlling for students' initial meta-skills [F(1,61) = 313.996, p 0.001, np2 = 0.84]. Based on these findings, it can be concluded that the implementation of the research-based project (RBP) model has a substantial or highly effective impact on enhancing undergraduate students' meta-skills.